Ukrainian Migration Aspirations towards Germany: Analysis and Development Scenarios - Vitalii Boiko; Olha Mulska; Ihor Baranyak; Olha Levytska (Comparative Economic Research. Central and Eastern Europe, 2021)
Based on the multiple regression model and scenario approach to forecasting, the ar- ticle estimates the Ukrainian migration aspirations towards Germany (the scale of migration, the economic activity of migrants, and their economic benefits). It is argued that major transformations in the gender-age structure of the German population may cause a demographic crisis and labour market imbalances. Our projections indicate the growing role of foreign human resources in the German economy. When modelling the scale of emigration from Ukraine, an integrated approach is applied, considering not only trends of pull-push factors but also special aspects of the German migration policy and the outflow of 8-10 million Ukrainian migrant workers. Given the poor statistical data on the scale of labour emigration needed for constructing reliable econometric models, the use of expert forecasting method remains the most optimal technique for assessing potential migration flows and migration systems.
Keywords: F22; J11; O15; 330; migration aspirations; socio-economic factors; forecast; migration policy; Ukraine; Germany